Implementation of the TENANG Method as a Participatory Educational Approach in Self-Monitoring of IUD Strings - Annisa Andriyani; Indarwati Indarwati; Tri Susilowati; Anjar Nurrohmah (Media of Health Research, 2026)
The intrauterine device (IUD) is a highly effective long-term contraceptive; however, failure still occurs, often due to limited acceptor involvement in routine self-monitoring. Existing educational approaches tend to focus on information delivery and lack structured, participatory components that support consistent self-monitoring practices. This study aims to analyze the effectiveness of the TENANG (Find the Thread) method as a participatory educational approach to improve knowledge and the application of IUD string self-monitoring among contraceptive acceptors. A quasi-experimental design with a one-group pre-test and post-test was used with 336 IUD acceptors in Banjarsari District. The intervention was conducted over three months using structured education and monitoring tools. The results showed a significant increase in knowledge after the intervention (χ² = 325.000; p < 0.001), with 94.9% of respondents attaining a high level of knowledge. In addition, 75.3% of participants applied the TENANG method. Educational level was identified as a significant factor influencing implementation (p = 0.002). The study highlights the novelty of integrating participatory education with structured self-monitoring tools in improving contraceptive-related behavior. The TENANG method demonstrates potential as a practical and scalable approach to strengthen acceptor involvement and enhance the effectiveness of long-term contraceptive use.